Arte e criação artística em contexto urbano: um estudo de caso de política pública em Porto Alegre (RS, Brasil) - Ana Luiza Carvalho da Rocha; Cornelia Eckert (Ciências Sociais Unisinos)
n Porto Alegre the production of public art has been since 1991 an object of specific concern for the Coordination of Plastic Arts of the Municipal Department of Culture, which instituted the contest Espaço Urbano & Espaço Arte, a project that ended up directly influencing a series of cultural policies. It is worth mentioning the performance of one of its coordinators, who reports her experience with the origins of the contest and its unfolding as a public policy. It is a reflective essay on the place of public art in the contemporary urban space.